Development Strategy of Tourism Object in Borobudur, Magelang District - Rahadyan, Gentur Hutomo (Universitas Negeri Semarang, 2019)
This study aims to identify the contribution of new tourism objects around the Borobudur Temple area in increasing Magelang Regional Revenue (PAD), identifying driving and inhibiting factors to optimize the attractiveness of tourists in new tourist attractions around the Borobudur Temple, as well as develop integration strategies that can be carried out by the Magelang Regency government in developing new Tourism Objects around the Borobudur Temple using the SWOT analysis method. The expert respondents in this study were 2, namely Bappeda and the Magelang Regency Culture and Tourism Office. The results showed that the contribution given could boost the tourism sector to Magelang regency's regional income. It was seen from the percentage of contributions from several new tourism objects that were higher than the existing cultural tourism, Pawon and Mendut Temple. The inhibiting factor is road access to some tourist attractions in the less adequate district in Borobudur. The driving factor in the development of tourist attraction is the level of tourist arrivals has increased in each year (due to the) location of strategic tourist attractions and close to each other. The integration strategy of developing tourist attraction in Borobudur Subdistrict in order to increase the local revenue of Magelang Regency by optimizing the development of tourist attraction to become a superior tourist attraction in order to evenly distribute tourist visits to the Borobudur District is not only focused on Borobudur Temple. Penelitian ini bertujuan untuk mengidentifikasi kontribusi objek wisata baru di sekitar kawasan Candi Borobudur dalam meningkatkan Pendapatan Asli Daerah Magelang, mengidentifikasi faktor pendorong dan penghambat untuk mengoptimalkan daya tarik wisatawan di tempat wisata baru di sekitar Candi Borobudur, serta mengembangkan integrasi strategi yang dapat dilakukan oleh pemerintah Kabupaten Magelang dalam mengembangkan Objek Wisata baru di sekitar Candi Borobudur menggunakan metode analisis SWOT. Responden ahli dalam penelitian ini adalah 2, yaitu Bappeda dan Dinas Kebudayaan dan Pariwisata Kabupaten Magelang. Hasil penelitian menunjukkan bahwa kontribusi yang diberikan dapat meningkatkan sektor pariwisata untuk pendapatan daerah Kabupaten Magelang. Itu terlihat dari persentase kontribusi dari beberapa objek wisata baru yang lebih tinggi dari wisata budaya yang ada, Pawon dan Candi Mendut. Faktor penghambatnya adalah akses jalan ke beberapa tempat wisata di kabupaten Borobudur yang kurang memadai. Faktor pendorong dalam pengembangan objek wisata adalah tingkat kedatangan wisatawan yang meningkat setiap tahunnya (karena) lokasi tempat wisata yang strategis dan berdekatan satu sama lain. Strategi integrasi pengembangan objek wisata di Kecamatan Borobudur dalam rangka meningkatkan pendapatan daerah Kabupaten Magelang dengan mengoptimalkan pengembangan objek wisata.